Uric acid, as a double-edged sword, affects the activity of epidermal growth factor (EGF) on human umbilical vein endothelial cells by regulating aging process. Issue 2 (1st February 2022) - Li, Yuan; Zhao, Linru; Qi, Wufang
ABSTRACT: Uric acid (UA) is the main metabolite of the human body. Although UA is only a product of metabolism, it is important biological regulator. Epidermal growth factor (EGF) has important biological functions. However, so far, the effect of UA on EGF's activity has not been revealed. For this, in the current study, we systematically studied the effect of OA on the biological activity of EGF. Human Umbilical Vein Endothelial Cells (HUVECs) were used as an in vitro model, and Western-blot, RT-PCR, laser scanning confocal microscopy (CLSM) and co-localization analyses were carried out. The results showed that high concentration of UA (10 mg/dl) severely affected the biological activity of EGF. High concentration of UA suppressed the activity of EGF, and inhibited the biological effect of EGF on the HUVECs. However, it is interesting that EGF-mediated intracellular signaling was significantly down-regulated in the H2 O2 -induced senescent HUVEC, and physiological concentration of UA could at least partially restore the EGF-mediated signaling. Further work showed that physiological concentration of UA (5 mg/dl) shows the anti-aging effect. Taken together, current research indicates that UA may be a 'double-edged sword', physiological concentration of UA may be beneficial, but high concentrations of uric acid (UA) are harmful.